The spy who loved me - Fleming, Ian 1908-1964
Agent 007 joins forces with a beautiful Russian agent to battle a mad genius, multi-millionaire shipping magnate Karl Stromberg. Stromberg plans to destroy the earth and rebuild it underwater, and is in possession of an ultra- sensitive submarine tracking system which he seems to be offering to the highest bidder. After he captures a British submarine, Bond's job is to recover the tracking device and free the submarine.